Implementation of Learning Methods Role-Playing in Drama Materials to Improve Speaking Skills of Grade VIII Junior High School Students - Ruslan, Hasnur; killa, Syakilla; Nirmayanti, Nirmayanti; Yotolembah, Ade Nurul Izatti G (Institut Agama Islam Negeri Palopo, 2025)
The purpose of this study was to determine whether the role-playing learning method in drama material improved the speaking skills of class VIII students of MTs Al Khairaat Sindue. This study used a pre-experiment research design consisting of one class (one group), namely the experimental class. The sample of this study was the VIII grade students of MTs Al Khairaat Sindue; with a total of 12 students. Data collection was carried out by giving a tragedy drama script test consisting of pre-test and post-test conducted at the first and last meeting. The pre-test result of class VIII MTs Al Khairaat Sindue was 46.38 while the post-test result was 70.27. By applying a significant level of 0.05, the researcher found that the t-count value (8.62) was higher than the t-table (0.16). In conclusion, the implementation of the role-playing learning method in drama material is effective to improve the speaking skills of class VIII students of MTs Al Khairaat Sindue. Based on these results, it can be concluded that the role-playing learning method can be applied by teachers in the teaching and learning process as one of the effective learning methods to improve students' speaking skills, especially for grade VIII students of junior high school and senior high school.